Observation of Body‐Centered‐Cubic Cu Nanocluster with Partial Cu(0) Character - Pu Gao; Jing Du; Weijie Hong; Mingzai Wu; Yan Feng; Yanjun Ding; Manzhou Zhu (Small Structures)
The structure of nanoparticles is a key determinant of their material properties. The synthesis of non‐face‐centered‐cubic (FCC) Cu nanoclusters (NCs) with Cu(0) character is still challenging due to their instability. Herein, a Cu(0)‐containing Cu NC is first reported to contain a metallic framework of 23 Cu atoms with a body‐centered‐cubic Cu@Cu8 core, stabilized by 6 triphenylphosphine (TPP) and 18 4‐methylbenzenethiolate ligands, as determined by single‐crystal X‐ray crystallography. The observed structure stands in stark contrast to the FCC and other structures reported for Cu NCs. Moreover, this newly formed NC could react with Au+ ion with controlled concentration, rapidly yielding another identifiable and bright red‐emitting AuCu14 cluster upon irradiation. Based on this structural conversion, a new “turn‐on” type of photoluminescent probe can be developed for the detection of Au+ ion with an ultrafast response time (30 s) at a low detection limit (0.13 ppm). This work provides a new way of understanding the growth of metal clusters and exploring their applications in luminescent sensors.